Folic acid conjugated Fe3O4 magnetic nanoparticles for targeted delivery of doxorubicin. Issue 43 (12th October 2016) - Rana, Suman; Shetake, Neena G.; Barick, K. C.; Pandey, B. N.; Salunke, H. G.; Hassan, P. A.
Abstract : The development of water-dispersible Fe3 O4 magnetic nanoparticles having a carboxylic moiety for drug binding and an amine moiety for folate mediated drug targeting. Abstract : The interfacial engineering of magnetic nanoparticles (MNPs) with specific functional groups or targeting ligands is important for their in vivo applications. We report here the preparation and characterization of bifunctional magnetic nanoparticles (BMNPs) which contain a carboxylic moiety for drug binding and an amine moiety for folate mediated drug targeting. BMNPs were prepared by introducing bioactive cysteine molecules onto the surface of undecenoic acid coated Fe3 O4 magnetic nanoparticles (UMNPs) via a thiol–ene click reaction and then, folic acid was conjugated with these BMNPs through an EDC–NHS coupling reaction. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis indicate the formation of highly crystalline single-phase Fe3 O4 nanostructures. The changes in the interfacial characteristics of the nanoparticles and the presence of an organic coating are evident from Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering (DLS), zeta-potential measurement, and thermogravimetric analysis (TGA). These nanocarriers have an average size of 10 nm, and have a pH dependent charge conversional feature and protein resistance characteristic in physiological medium. These nanoparticles also show high loading affinity for an anticancer drug, doxorubicin hydrochloride (DOX) and its pH dependent release. This is highly beneficial for cancer therapy as the relatively low pH in tumors will specifically stimulate the drug release at the site of interest. Furthermore, our fluorescence microscopy and flow cytometry studies confirmed the higher cellular internalization capability of these folic acid conjugated nanoparticles in cancer cells over-expressing folate receptors.